Scratch to sensitize: scratch-induced sensitivity enhancement in semiconductor thin-film sensors. Issue 32 (7th August 2019) - Lee, Geonhee; Choi, Min; Chae, Soo Sang; Jeong, Du Won; Choi, Won Jin; Ji, Seulgi; Kim, Yun Ho; Choi, Ji Woon; Lee, Tae Il; Cho, Incheol; Park, Inkyu; Lee, Sun Sook; et al.
Abstract : Nanoscale scratches were produced with mechanical abrasion to enhance the chemical sensitivity of thin-film-type semiconductor sensors; ZnO sensor devices with well-aligned arrays of scratches exhibited superior performance. Abstract : Semiconductor gas sensors are advantageous in miniaturization and can be used in a wide range of applications, yet consume large power due to high operating temperature. Here we demonstrated the ability of nanoscale scratches produced with mechanical abrasion to enhance the chemical sensitivity of thin-film-type semiconductor sensors. Well-aligned arrays of scratches parallel to the electrical current direction between the source and drain electrodes were made, using typical polishing machines with diamond suspensions, on semiconductor thin films produced with various deposition methods such as atomic layer deposition (ALD), sputtering, and the sol–gel technique. Processing with sharp diamond microparticles left nano-grooves on the surface, together with changes in chemical composition. For all of the tested metal oxide thin films, the introduction of scratches yielded increased quantities of oxygen vacancies and metallic components. Scratched ZnO devices exhibited superior performance even at room temperature, as predicted by a computational simulation that showed increased binding energy of gas molecules on defects. The scratch technique shown in the present study may be used to produce dense arrays of nanometer-scale, chemically functionalized line patterns on substrates larger than a few tens of centimeters with minimum cost, which in turn may be used in a variety of applications including massive arrays of sensors displaying high sensitivity.